Respostas
respondido por:
17
Oi,
Resolução
5y-6=2(y+9)
5y - 6 = 2y + 18
5y - 2y = 18 + 6
3y = 24
y = 24/3
y = 8
Espero ter ajudado e bons estudos !
Resolução
5y-6=2(y+9)
5y - 6 = 2y + 18
5y - 2y = 18 + 6
3y = 24
y = 24/3
y = 8
Espero ter ajudado e bons estudos !
isabellaybarra:
ogd :) :) <3
respondido por:
11
Oi,
5y - 6 = 2(y + 9)
5y - 6 = 2y + 18
5y - 2y = 6 + 18
3y = 24
y = 24
3
y = 8
Espero ter ajudado :)
5y - 6 = 2(y + 9)
5y - 6 = 2y + 18
5y - 2y = 6 + 18
3y = 24
y = 24
3
y = 8
Espero ter ajudado :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás